Participação do peptídeo natriurético atrial na hipotensão e bradicardia de ratos espontaneamente hipertensos após treinamento físico crônico em diferentes modalidades - Endlich, Patrick Wander (2009)
Background – Acutely the atrial natriuretic peptide (ANP) has an effect of renal natriuresis and diuresis, vasodilatation, resulting in decrease of blood pressure. However, the responses of this peptide and of his receptors associated to different chronics physical training in the hypertension remain unknown. Methods and results - The aim was identified the possible alterations in the synthesis and release of atria ANP, expression and affinity of the NPR-A, NPRC in the kidneys and fat tissue of spontaneously hypertensive rats (SHR) submitted to swimming or running physical training. Male SHR were subjected to 8-week of swimming or running under similar intensities. Radioimmunoassay was used to measure ANP levels. mRNA ANP in the atria, such as mRNA of natriuretic peptide receptor (NPR)-A and NPR-C in the kidneys and fat tissue was determined by real time- polymerase chain reaction. The autoradiography was used to determine the sensitivity of binding to ANP receptors. Both groups shown decrease in the blood pressure, but only swim group shown bradycardia. A significant increase of ANP expression in the right atrium and plasma levels was found in the swim group. Hence, not was found alteration in the expression of NPR-C in fat tissue, but the binding of ANP was altered in this tissue in the swim group. The index between NPR-A/NPR-C in the kidneys was significantly lower in run group. Conclusions: The mechanism hypotensor and bradycardic in hypertensive rats shown differences, with the ANP can be involved in this alterations by swimming, but not in the running training.